PENGEMBANGAN SISTEM SMS PENGADUAN MENGGUNAKAN SMS GATEWAY UNTUK MENINGKATKAN KINERJA PNPM MANDIRI PERDESAAN KABUPATEN BULELENG BERBASIS WEB - Putu Agus Eka Wilantara; I Gede Mahendra Darmawiguna; Made Windu Antara Kesiman (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
This research aims to design and implement a system of SMS Charges using the SMS Gateway to improve Self-service PNPM Mandiri Perdesaan Buleleng Regency Web based. This research is expected to help communities and agencies in providing oversight to PNPM Mandiri Perdesaan runs well. In the event of breaches of the community are expected to promptly report such violation to the institution.This research is research development made to build an application development system SMS Using SMS Gateway Complaints to improve the performance of the PNPM Mandiri Perdesaan Buleleng Regency, where Web-based applications can eventually accommodate data from public complaints about the problems of the PNPM Mandiri Perdesaaan that occur in field. Complaint SMS system development using SMS Gateway PNPM Mandiri Perdesaan Buleleng Regency Web-based use Model Waterfall and designed using Data Flow diagrams (DFD).Complaint SMS system development using SMS Gateway PNPM Mandiri Perdesaan Buleleng Regency this Web Based programming language implemented using PHP and MySQL as the database and application to run as Gammu SMS Gateway. After going through the process of testing, it can be concluded that the applicationis able to provide information about problems that occur in the field sent via SMS.